2016
DOI: 10.1002/fam.2405
|View full text |Cite
|
Sign up to set email alerts
|

School egress data: comparing the configuration and validation of five egress modelling tools

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions? Contact the NRC Publications Archive team atPublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. If you wish to email the authors directly, please see the first page of the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 11 publications
0
23
0
1
Order By: Relevance
“…This is done by selecting those values from existing databases, when available, (see for instance [1][2][3]) or by making reasonable assumptions. Evacuation data is therefore needed to model and simulate occupants' behaviour [4,5] as well as to validate existing and new evacuation models [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…This is done by selecting those values from existing databases, when available, (see for instance [1][2][3]) or by making reasonable assumptions. Evacuation data is therefore needed to model and simulate occupants' behaviour [4,5] as well as to validate existing and new evacuation models [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The proposed method assumes that there are three possible exit and access points, both for flights and landings of stairs—inside, center, and outside—similarly to the proposal of Cuesta et al 10 …”
Section: The Proposed Methodsmentioning
confidence: 99%
“…Cuesta and Gwyne 10,14,15 found that there was variability in the routes taken by people on landings, and consequently, the possibility of significant variation in speeds, so that they have expanded the possible routes on the landings of stairs to three. However, they did not present further details about the speeds resulting from this variable.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 shows the histograms of the observed data. The analysis also included datasets collected during a semi-announced evacuation trial in a school building [16,17] (i.e. students had no warning, while the teaching staff had some prior warning in the trial).…”
Section: Datasetsmentioning
confidence: 99%
“…Datasets are usually presented in the following format: average, standard deviation, maximum and minimum values. Information such as sample sizes, data collection techniques and the background conditions are occasionally provided [16,17]. Nevertheless, in most cases, neither the raw data is available nor the type of PDF is defined.…”
Section: Introductionmentioning
confidence: 99%